GEIKIMIA UNSUR-UNSUR TANAH JARANG DAN YTRIUM (REY) PADASISTEM HIDROTERMAL VULKANIK DI DAERAH KOMPLEKS GUNUNG APIBANDUNG JAWA BARAT - Susanna, Nelly
Rare earth elements (REE) and yttrium (Y), henceforth called REY, present in geothermal waters as conservative trace elements. Water maintains its REY abundance along the pathway, so REY can be used as tracer of origin of fluid in a hydrothermal system. Research on REY content in hydrothermal system is very limited, so it is necessary to conduct a research on the characteristic of REY especially in volcanic hydrothermal system. Research was conducted in West Java, in volcanic hydrothermal systems of Bandung Volcanoes Complex. Concentration of REY in water and rock/sediment is determined with ICPMS Agilent 7700x. Methods of analysis that was selected are using HF/HClO4 to digest rock/sediment samples and 2-ethylhexyl phosphate solution to preconcentrate the REY concentration in water samples. Thirty two samples consist of 16 water and 16 surrounding rocks samples are collected from geothermal manifestations in research area. Anion content in water influences REY abundance pattern of water and water-rock interaction at geothermal manifestation of volcanic hydrothermal system hence water samples are categorized into Cl water, acid volcanic condensate, SO4 and HCO3 steam condensate. Chloride waters contain 0.01-17.46 ng/g REY; acid volcanic condensates contain 0.32-158.98 ng/g REY; and SO4 and HCO3 steam condensates contain 0.01-133.15 ng/g and 0.01-5.66 ng/g REY consecutively. Surrounding rock samples are categorized into soil, silica sinter, travertine sinter, pyroclastic rock, and lake deposit which contain 23.00-5553.14 ng/g; 51.60- 34995.20 ng/g; 0.06-12806.44 ng/g; 41.47-112007.08 ng/g; and 0.55-27754.53 ng/g REY consecutively. Geothermal waters are originated from meteoric fluids and meteoric fluids that mix with magmatic fluids. REY concentration in water is influenced by pH, water with lower pH has higher REY concentration. REY concentration in water is not influenced by temperature variance.